2011
DOI: 10.1103/physrevb.84.235428
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium quantum transport in fully interacting single-molecule junctions

Abstract: Using non-equilibrium Green's functions, we derive a formula for the electron current through a lead-molecule-lead nanojunction where the interactions are not restricted to the central region, but are spread throughout the system, including the leads and the lead-molecule interfaces. The current expression consists of two sets of terms. The first set corresponds to a generalized Meir and Wingreen expression where the leads' self-energies are renormalized by the interactions crossing at the molecule-lead contac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 37 publications
0
55
0
Order By: Relevance
“…For the purpose of the present section, we then use the NEGF approach as the calculations are more straightforward in the non-interacting case. We also note that the NEGF formalism permits us to include local interaction in the central region in a compact and self-consistent scheme, as we have done in [22,[61][62][63][64][65][66][67].…”
Section: An Examplementioning
confidence: 99%
“…For the purpose of the present section, we then use the NEGF approach as the calculations are more straightforward in the non-interacting case. We also note that the NEGF formalism permits us to include local interaction in the central region in a compact and self-consistent scheme, as we have done in [22,[61][62][63][64][65][66][67].…”
Section: An Examplementioning
confidence: 99%
“…In Refs. [73,74], we showed that for a finite applied bias V the steady-state current I L (V ) flowing through the left LC interface is given by:…”
Section: General Theory For Quantum Transportmentioning
confidence: 99%
“…In a recent paper we derived a general expression for the current in nano-scale junctions with interaction present everywhere in the system 73 . With such a formalism, we can calculate the transport properties in those systems where the interaction is present everywhere.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the techniques developed to deal with SR interactions are not directly exportable to study LR ones. 15 The difficulty stems from the impracticability of combining many-body methods with embedding techniques, hence reducing the problem to the evaluation of the Green's function of a finite and interacting open system. 16,17 Recently Elste and coworkers 18 approached the problem using the rate equations (REs) method in the IRLM with Luttinger liquid leads.…”
Section: Introductionmentioning
confidence: 99%